Intensity of trematode metacercariae in cyprinoid fish in Chiang Mal Province, Northern Thailand - Sukontason K.L. (2014)
The intensity of infection of trematode metacercariae was determined in five species of cyprinoid fish collected from Mae Ngud reservoir, Chiang Mai Province. These species were Thynnichthys thynnoides, Puntioplites proctozysron, Hampala macrolepidota, Puntius leiacanthus and Puntius gonionotus. T. thynnoides contained the highest number (83.0%) of metacercariae, whereas P. gonionotus had the fewest (0.19%). The caudal fin was the area of highest infection of metacercariae (49.39 %) with the anal fin having the fewest (5.93%). Most metacercariae was isolated from Haplorchis taichui (63.27%), with an intensity variation of 0.3-165.2 metacercariae/fish.